School Financial Management for Facilities and Infrastructure at Elementary School - Choirun Nisa; Aulia Kharisma; Retno Fadillah; Rizka Silvia Fatmawati (Proceedings Series on Social Sciences & Humanities, 2023)
This study aimed to analyze and understand financial management at SD Muhammadiyah 22 Surakarta Elementary School (M22SES), Central Java, Indonesia. This study used a qualitative descriptive method, which aims to describe financial management and its relation to the management of school infrastructure. The authors collected data through observation, interviews, and documentation. The data were separated according to categories to obtain a conclusion. The results of this study showed that (1) financial management was well managed for the budget for facilities and infrastructure, (2) the school budget was planned for existing facilities and infrastructure, conditional or stable organization and is monitored in schools, (3) facility management and infrastructure of M22SES were controlled by bookkeeping so it can assist in procuring facilities and infrastructure as well as managing financial management